Fungal Systematics and Evolution: FUSE 8 - Lebeuf, Renée (2021)
In this 8th contribution to the Fungal Systematics and Evolution series published by Sydowia, the authors formally describe 11 species: Cortinarius caryae, C. flavolilacinus, C. lilaceolamellatus, C. malodorus, C. olivaceolamellatus, C. quercophilus, C. violaceoflavescens, C. viridicarneus, Entoloma meridionale (Agaricales), Hortiboletus rupicapreus (Boletales), and Paraglomus peruvianum (Paraglomerales). The following new country records are reported: Bolbitius callistus (Agaricales) from Russia and Hymenoscyphus equiseti (Helotiales) from Sweden. Hymenoscyphus equiseti is proposed as a new combination for Lanzia equiseti, based on ITS and LSU sequence data in combination with morphological study.